Unlocking Performance in Public Organizations: The Mediating Role of Employee Engagement in Talent and Knowledge Management - Pangastiting Nalar, Dhimas Agung; Irawanto, Dodi Wirawan; Azzuhri, Misbahuddin (Jurnal Aplikasi Manajemen, 2025)
The Directorate General of Customs and Excise (DGCE) is one of the Directorates General within the Ministry of Finance responsible for formulating and implementing policies in the areas of supervision, law enforcement, services and facilities, and optimization of state revenue in the areas of customs and excise in accordance with the provisions of laws and regulations. However, even though DGCE is a government agency, its performance still needs to be optimized. The purpose of this study is to analyze the impact of talent management and knowledge management on organizational performance in public organizations. Employee engagement in this study is expected to contribute to state revenue growth, thereby boosting the Indonesian economy. A quantitative technique was used in an explanatory research design. Using proportionate stratified random sampling, 303 respondents were chosen from among 912 Heads of Offices and Heads of Subdivisions/Sections throughout Indonesia. Likert scale surveys were used to gather data. Structural Equation Modeling Partial Least Squares (SEM-PLS) was used to do the analysis. Generational differences were also tested using multi-group analysis (MGA). The findings demonstrate that knowledge and talent management directly enhance organizational performance. Employee engagement can mediate the relationship between talent management and knowledge management on organizational performance. MGA results, however, show no discernible generational differences. The novelty of this study lies in comparing the public and private sectors. These results contribute to the body of study on human resource management in public institutions and offer recommendations to enhance DGCE's talent management, knowledge management, and employee engagement.